THE EFFECT OF POPULATION, GRDP, AND INVESTMENT ON EMPLOYMENT IN NORTH SULAWESI PROVINCE - Pertiwi, Liza Tri Yudha; Islami, Fitrah Sari (Transpublika Publisher, 2022)
This research aims to determine the effect of Population, Gross Regional Domestic Product (GRDP), and Investment on employment in the short and long term in North Sulawesi Province. The data used are times series data from 2001-2021 sourced from BPS. The method used in this article is Error Correction Model (ECM). The results revealed that the population has a positive and insignificant effect on employment in the short term, while in the long term it has a positive and significant effect on employment, GRDP has a positive and insignificant effect on employment in the short term, while in the long term it has a negative and insignificant effect on employment, investment has a positive and significant impact on employment in the short term, while in the long term investment has a positive and significant impact on employment.